2012
DOI: 10.1039/c2em10999a
|View full text |Cite
|
Sign up to set email alerts
|

Verification of a depth-integrated sample arm as a means to reduce solids stratification bias in urban stormwater sampling

Abstract: A new water sample collection system was developed to improve representation of solids entrained in urban stormwater by integrating water-quality samples from the entire water column, rather than a single, fixed point. The depth-integrated sample arm (DISA) was better able to characterize suspended-sediment concentration and particle size distribution compared to fixed-point methods when tested in a controlled laboratory environment. Median suspended-sediment concentrations overestimated the actual concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Clark and Siu (2008) identified several studies that showed that measurements of TSS generally were 20%-40% lower than corresponding SSCs for identical samples analyzed with different methodologies. This seems to indicate that SSC is a better measure of suspended solids, especially with the use of a DISA (Selbig et al 2012), which compensates for solids stratification. However, because TSS often is used by environmental regulators to define suspended solids, solids commonly are measured using both TSS and SSC.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Clark and Siu (2008) identified several studies that showed that measurements of TSS generally were 20%-40% lower than corresponding SSCs for identical samples analyzed with different methodologies. This seems to indicate that SSC is a better measure of suspended solids, especially with the use of a DISA (Selbig et al 2012), which compensates for solids stratification. However, because TSS often is used by environmental regulators to define suspended solids, solids commonly are measured using both TSS and SSC.…”
Section: Discussionmentioning
confidence: 93%
“…Once a water-level threshold was exceeded, typically a depth of 1.2 cm from the pipe floor, the volume of water passing the station was measured and accumulated at 1-min increments until a volumetric threshold was reached. At that point, a depth-integrated sample arm (DISA) sampler (Selbig et al 2012) in both the influent and effluent pipes collected a discrete water sample and the volumetric counter was reset. Sample collection in the effluent pipe occurred approximately 1 min after sample collection in the influent pipe.…”
Section: Sample Collection and Measurement Of Dischargementioning
confidence: 99%
See 1 more Smart Citation
“…This is an important distinction from NURP sample collection methods, which acquired a water sample from a single point in the water column. Laboratory testing showed that the DISA was able to measure sediment concentrations within 7 percent of the true value [27]. The DISA has been used to improve the characterization of sediment concentrations and PSDs in urban stormwater runoff from several different urban source areas and land uses that have consistently shown large departures from the NURP PSD [6].…”
Section: Measured Distributions Using Improved Sample Collection Techmentioning
confidence: 99%
“…However, potential concentration gradients should be considered, especially for constituents commonly associated with larger particulates (Taylor et al 2005;Harmel et al 2003Harmel et al , 2006a. Although it is likely unnecessary at EOF sites, a vertical intake with multiple entry points or a depth-integrated sampling arm could be employed to better capture vertical concentration gradients (Gettel et al 2011;Selbig et al 2012). Where this is not feasible, the relationship between concentrations at the intake and in the total cross-section can be established for the range of expected discharges (Ging 1999).…”
Section: Automated Samplers (Electronic)mentioning
confidence: 99%